Monitoring System Of Parking Land Availability And Number Of Cars In Web-Based Parking Place On The Smart Parking System - Miftavinda Farah Diba (JAICT, 2021)
According to data obtained from the website www.bps.go.id, the total number of motorized vehicles in Indonesia in 2018 was 146,858,759. The result of the increase in the number of motorized vehicles is that it is increasingly difficult to find parking space. People also often experience difficulties when finding which parking lot is still empty because there is no information about the state of the parking lot. Based on these problems, people need a system to check the parking lots available by utilizing the Internet of Things (IoT). Smart Parking Monitoring System is a web-based parking monitoring system that displays real-time parking availability information. The data was collected by simulating parking the car in the parking lot. Monitoring data transmission from the sensor node to the server is done using Wireshark software. The test results of the propagation time that occur in the data transmission process for an interval of 1 minute 15 seconds and the 5-second data transmission interval are 5053 milliseconds. The average value of the propagation time that occurs in the process of receiving data from the server is 197 milliseconds.